The Relationship Between The Length of Labour and The Taking Hold of Post Partum Mothers - Yulianti, Yulianti; Irmayanti; Darwin, Devi (Universitas Islam Jember, 2024)
The intermediate puerperium (taking hold) is a period of complete recovery of the genitalia, which lasts about 6-8 weeks. The taking hold phase shows the emotional changes that mothers feel after becoming mothers and after mothers see their babies for the first time and experience caring for babies. The Taking Hold phase is a post partum period that lasts between 3-10 days. This study aims to relate the length of labour with the taking hold of postpartum mothers in the Ponrang Health Centre working area in 2023. The research design used Cross Sectional. The research subjects were all postpartum mothers in June-July 2023, 87 people. Based on the results of the chi-square statistical test using the Statistical Program for Social Science (SPSS) application, the relationship between the length of labour with the taking hold of postpartum mothers obtained a p value = 0.003 < α = 0.05 which means that there is a relationship between the length of labour with the taking hold of postpartum mothers.